THE IMPACT OF EDUCATIONAL TECHNOLOGY AND FREQUENCY OF USAGE - Safwaan Zamakda Allison (Universitas Nasional, 2022)
This paper aims to research the various forms of technology integrated into Saudi Arabia’s educational system and to determine how they have been used to enhance learners’ achievements in schools. The study was conducted on 325 students studying political science in five different universities in Saudi Arabia’s capital Riyadh. Samples of students were taken from King Saud University, Prince Sultan University, Shaqra University, Al Yamamah University, and Majmaah University. An online survey on the application of technology in education was sent to all the respondents of the study. To determine the frequency of technology usage and its impact on students’ achievements, the correlation rank coefficient, and descriptive statistics were used. In all five learning institutions, the study revealed a significant relationship between students’ use of technology and their achievements in class. According to the study, 58% of the students used laptops in their learning activities, 35% used mobile devices, 5% used tablets, and 0.5% used desktop computers. This paper details the results of the study to show how technology is used among political science students in the country, and the benefits associated with it. The use of technology in learning processes produces substantial benefits, compared to not utilizing assistive technologies. Nonetheless, further research is required to determine the scale of success associated with educational technology.